Currency Redesign Policy and Ease of Doing Business in Nigeria: Tracing the Implications on the Informal Sectors of the Economy - Amobi P. Chiamogu; Uchechukwu P. Chiamogu (CV. Era Digital Nusantara, 2025)
Abstract: This study examines the implications of Nigeria’s 2022 currency redesign policy on the ease of doing business in the informal sector. Given that the informal sector contributes significantly to Nigeria’s GDP and employment, the abrupt implementation of the policy created liquidity constraints, disrupted transactions, and heightened financial exclusion risks. The study highlights the challenges faced by small traders and daily wage earners who rely heavily on cash-based transactions. It also evaluates the broader economic consequences of the policy, including its impact on market confidence, consumer spending, and business sustainability. Purpose: The research aims to assess the effects of the 2022 currency redesign policy on business operations within Nigeria’s informal sector. It explores how liquidity shortages, limited access to financial services, and the lack of digital transaction infrastructure affected business continuity and economic stability. Design/Methodology/Approach: This study employs a documentary research method, analyzing secondary data from policy reports, economic studies, and government publications. A qualitative approach is used to evaluate the economic implications of the currency redesign, focusing on transaction efficiency, financial inclusion, and business resilience. Findings: The study finds that the sudden withdrawal of old naira notes, without a sufficient supply of new currency, severely impacted the informal economy. The policy led to a liquidity crisis, reduced business activity, and forced many traders to suspend operations. Furthermore, while digital transactions increased temporarily, financial infrastructure limitations hindered long-term adoption. The findings emphasize the need for gradual implementation strategies and improved financial inclusion measures to prevent economic disruptions. Originality/value: This study contributes to the discourse on monetary policy and economic stability by providing a focused analysis of how currency redesign policies affect the informal sector. It offers insights into the challenges of implementing monetary reforms in cash-dependent economies and highlights policy recommendations to mitigate adverse effects on business operations.